PENGARUH SENAM AEROBIK LOW IMPACT TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI - Roza ' Fetriwahyuni; Siti ' Rahmalia; Herlina ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Variety of things have been found to control blood pressure, one of which is low impact aerobic exercise in particular. Exercise low impact aerobics gymnastics movements is suitable for people who has heart disease and hypertension . This excercise has slow moving and can be do by anyone. The purpose of this study was to determine the effect of low impact aerobic exercises on blood pressure among patients with hypertension. This study used quasy experiment design with non-equivalent control group approach. This study conducted  at Tenayan Raya public health center with 34 samples, which is divided into 17 experimental group and 17 control group. The experiment group was given low impact aerobics. The instruments used in this study was digital sphygmomanometer and observation sheet. The data was analyzed univariate and bivariate  which is show frequency and percentages and bivariate analysis with dependent t test and independent t test. the results of this study showed mean that degression of systolic and distolic blood pressure occur on experiment group about 11.53 mmHg and 9.58 mmHg. There was decrease mean sistolic and diastolic of blood pressure after intervention by low impact aerobic excercise. There was very significantly decrease for blood pressure among hypertension patient (p value = 0.000). The results showed low impact aerobics to effectively lower blood pressure in patients with hypertension. Based on the result of study, the researcher suggest that low impact aerobic excercise need to regular program for hypertension patient.